Problem solving skills and childhood traumas in patients who self-injured by punching glass during an anger outburst. Issue 1 (2010) - Özen, Şakir; Subaşı, Mehmet; Yıldırım, Azad; Baştürk, Mustafa; Bez, Yasin
No abstract available